A Data-Driven Approach to Improve the Digital Customer Journey for SMEs - A Case Study On HAILO - Caroline Heins; Daniela Grumbach; Deniz Herkert; Wolfgang H. Schulz (Marketing Review St.Gallen, 2021)
In the current, rapidly changing environment, understanding the customer journey and continuously improving the customer experience are key success factors for competing successfully in the online business. A case study of HAILO, a German-based OEM, shows the impact of a data-driven approach and derived activities on providing a customised digital experience in order to be successful in the digital age.
Keywords: 650